PENDIDIKAN KARAKTER QUR’ANI REAKTUALISASI PENDIDIKAN KARAKTER QUR’ANI (SEJARAH DAN TANTANGAN PENDIDIKAN ISLAM DI ERA GLOBAL) - Mujiburrahman Moh. Subhan; umar faruq (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2021)
Character education itself was once heralded as one of the priority programs of the leadership of President Joko Widodo who was still accompanied by Jusuf Kalla as vice president. The idea of PPK (Strengthening Character Education) was formulated and then rolled out in 2016. This is an effort to improve and solution to the condition of education in Indonesia. In fact, the Qur'an is the main source of reference to Islamic teachings therefore, during the construction of Islamic religious education in Makkah the Prophet taught the Qur'an. From the flashback of historical facts above we know the Prophet Muhammad SAW only by capitalizing on the Qur'an as learning material managed to change the character of the Arab nation that was previously very synonymous with deviations into a cultured, civilized and institutionalized nation and society. The education of qur'ani character in general contains three main values that are oriented on aspects of morality, among others: Morality towards God, fellow human beings and the universe. The three aspects of morality become the core of the Qur'an character education.